2014
DOI: 10.4103/1658-354x.125964
|View full text |Cite
|
Sign up to set email alerts
|

When place and time matter: How to conduct safe inter-hospital transfer of patients

Abstract: Inter-hospital transfer (IHT) of patients is often needed for diagnostic or therapeutic interventions. However, the transfer process carries its own risks as a poorly and hastily conducted transfer could lead to adverse events. In this article, we have reviewed literature on the key elements of IHT process including pre-transfer patient stabilization. We have also discussed various modes of transfer, physiological effects of transfer, possible adverse events and how to avoid or mitigate these. Even critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
0
47
0
5
Order By: Relevance
“…An interhospital patient transfer occurs when a patient discharged from one ("sender") hospital is admitted to another ("receiver") hospital in the same calendar day. Inter-hospital patient transfers are an essential component of health care systems (Sethi & Subramanian, 2014). Proliferation of specialties and regionalization of specialized care have contributed to an increase in inter-hospital patient transfers (Wagner et al, 2013).…”
Section: The Multilevel Social Space Of An Organizational Field Of Homentioning
confidence: 99%
“…An interhospital patient transfer occurs when a patient discharged from one ("sender") hospital is admitted to another ("receiver") hospital in the same calendar day. Inter-hospital patient transfers are an essential component of health care systems (Sethi & Subramanian, 2014). Proliferation of specialties and regionalization of specialized care have contributed to an increase in inter-hospital patient transfers (Wagner et al, 2013).…”
Section: The Multilevel Social Space Of An Organizational Field Of Homentioning
confidence: 99%
“…These results are contrary to those found in this study, where respiratory diseases appear in fifth place. Septic shock was the most common diagnosis reported by Sethi and Subramanian (2014). This difference in results may be associated with the response capacity of the Intensive Care Unit of the Hospital Unit of Bragança to treat patients with immunological/infectious and respiratory diseases, not needing to transfer them.…”
Section: Characterization Of the Clinical Profilementioning
confidence: 99%
“…International studies (Etxebarría et al, 1998;Kulshrestha & Singh, 2016) have documented the risk inherent to patient transport. Sethi and Subramanian (2014) have concluded that patients with a risk score ≥7 are at high risk for critical events and subsequent mortality. In this case, continuity of care should be maintained during the inter-hospital transport, and the team must be trained and qualified to anticipate, manage, and resolve any technical and medical difficulties that may arise during transport.…”
Section: Transport Risk Scorementioning
confidence: 99%
“…Inter-hospital patient transfers are an integral component of the Italian health care system, and of health care institutions more generally (Sethi and Subramanian, 2014). Over the last decades the health care literature has devoted increasing attention to patient transfers by focusing not only on their associated costs and clinical risks, but also on the critical role they play in ensuring the best possible care to patients (Hains et al, 2011).…”
Section: Figure 1 Map Of Abruzzo Hospitals 2003-2007mentioning
confidence: 99%